1992
DOI: 10.1063/1.108190
|View full text |Cite
|
Sign up to set email alerts
|

Microsecond lifetimes and low interface recombination velocities in moderately doped n-GaAs thin films

Abstract: Articles you may be interested inLow resistivity ohmic contacts to moderately doped nGaAs with lowtemperature processing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Taking into account the rate equation dn/dt = G eh − n/τ = 0, then n = G eh τ , where n is the number of electron-hole pairs generated by laser irradiation with no strain effect and τ is the nonradiative recombination lifetime. Referring to the literature, 16 the order of τ in GaAs is 1 × 10 −7 -1 × 10 −6 s, which is close to the experimentally obtained response time of the backaction force (1.6 × 10 −7 s). If we assume τ = τ ave = 1.6 × 10 −7 s (Fig.…”
Section: Appendix B: Estimation Of the Optopiezoelectric Effectsupporting
confidence: 87%
See 1 more Smart Citation
“…Taking into account the rate equation dn/dt = G eh − n/τ = 0, then n = G eh τ , where n is the number of electron-hole pairs generated by laser irradiation with no strain effect and τ is the nonradiative recombination lifetime. Referring to the literature, 16 the order of τ in GaAs is 1 × 10 −7 -1 × 10 −6 s, which is close to the experimentally obtained response time of the backaction force (1.6 × 10 −7 s). If we assume τ = τ ave = 1.6 × 10 −7 s (Fig.…”
Section: Appendix B: Estimation Of the Optopiezoelectric Effectsupporting
confidence: 87%
“…(2a) and (2b), the response time is given by The resulting τ ave is on the order of the nonradiative recombination lifetime in GaAs. 16,17 This also suggests that this dynamic backaction is associated with the spatial separation of electrons and holes. We also performed a direct measurement of the response time by applying a modulated Ti:Sa laser beam.…”
Section: Response Timementioning
confidence: 97%
“…1) are two popular materials for high efficiency solar cells. It has been found that many materials, such as AlGaAs and GaInP, [2][3][4][5][6] provide sufficient carrier confinement to GaAs, which prevents carriers from reaching the top surface of the epilayers and thus effectively reduces the surface recombination rate by providing a heterojunction interface. The interface recombination velocity (IRV) of a high quality GaAs/Al 0.5 Ga 0.…”
mentioning
confidence: 99%
“…Landauer's first criticism is much more difficult to rebut. Photon recycling is not an unheard of concept in solid state systems [46,47,48,49] but it is difficult. The requirement that the pulse shape remain undistorted in any wave guide is a tall order.…”
Section: Connecting Toffoli-fredkin Gatesmentioning
confidence: 99%